2015
DOI: 10.1007/s00442-015-3329-z
|View full text |Cite
|
Sign up to set email alerts
|

Diverse patterns of stored water use among saplings in seasonally dry tropical forests

Abstract: Tree species in seasonally dry tropical forests likely vary in their drought-survival mechanisms. Drought-deciduousness, which reduces water loss, and low wood density, which may permit dependence on stored water, are considered key traits. For saplings of six species at two distinct sites, we studied these and two associated traits: the seasonal amount of water released per stem volume ("water released") and the hydraulic capacitance of the stem (C). Two deciduous species with low stem density, Cavanillesia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 49 publications
1
32
0
2
Order By: Relevance
“…When plants were leafless, terminal twigs were collected to measure twig water potential (Ψ twig ) following the same protocol as for Ψ leaf , except that Ψ twig was measured only at predawn. Comparisons with psychrometric measurements of Ψ twig confirmed that the pressure chamber measurements accurately assessed Ψ twig (Wolfe & Kursar, ). As water potential is under a gradient within transpiring plants, we took the mean of Ψ leaf at predawn and midday to represent Ψ plant for each sapling in each census.…”
Section: Methodsmentioning
confidence: 53%
See 3 more Smart Citations
“…When plants were leafless, terminal twigs were collected to measure twig water potential (Ψ twig ) following the same protocol as for Ψ leaf , except that Ψ twig was measured only at predawn. Comparisons with psychrometric measurements of Ψ twig confirmed that the pressure chamber measurements accurately assessed Ψ twig (Wolfe & Kursar, ). As water potential is under a gradient within transpiring plants, we took the mean of Ψ leaf at predawn and midday to represent Ψ plant for each sapling in each census.…”
Section: Methodsmentioning
confidence: 53%
“…For Cavanillesia , direct measurements of stem water content revealed no difference between the wet and dry seasons, suggesting that leaf shedding contributed to the complete retention of stem water (Wolfe & Kursar, ). Meanwhile, Bursera had significantly lower stem water content in the dry season than in the wet season, suggesting that either leaf shedding did not stop water loss or that water loss occurred before leaf shedding (Wolfe & Kursar, ), and so it is unclear whether leaf shedding retained stem water. By contrast, Annona had Ψ plant that decreased at the onset of the dry season, before the saplings shed leaves, and then stabilized after leaf shedding (compare Figs c and S4c).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing WD results in a decrease of QW sat and Ψ dry season (which became more negative) (Oliveira et al ., ). Low WD enables species in dry habitats to store water in their stem and to flush new leaves at the onset of rain (Borchert et al ., ; Wolfe & Kursar, ; Wolfe et al ., ). Indeed, Oliveira et al .…”
Section: Discussionmentioning
confidence: 98%